South Africa / Michael R Brett, Philip Briggs, Brian Johnson Barker,... - Brett, Michael R
DK Eyewitness Travel Guide: South Africa is your in-depth guide to the very best of South Africa. From exploring the Palace of the Lost City to seeing the "Big Five" on safari in Kruger National Park to experiencing the multifaceted culture of a country with 11 official languages, visiting the "Rainbow Nation" is an adventure you will never forget.